Modeling the frame of a unique building of parametric architecture based on the application of the "cylinder-cylinder" surface - E. K. Agakhanov; M. K. Agakhanov; E. V. Trufanova; A. Z. Dzhabrailov (Вестник Дагестанского государственного технического университета: Технические науки)
Objective. The article considers information modeling of the frame of a unique building of parametric form in the software packages SAPFIR and LIRA-SAPR. This type of architecture is just beginning to develop in Russia, unlike other large cities of the world, which is becoming dominant.Method. At the first stage, the formation of a rotary surface with axoids "Cylinder-cylinder" formed by a straight line intersecting the axis of the movable cylinder, during external rolling, was considered. Varying the parameters made it possible to obtain a number of surfaces suitable for creating a parametric form of the frame of a unique building. A surface with five convex parts is adopted. The streamlined shapes of the object allow optimizing wind flows and protect against the formation of snow bags, which is relevant.Result. A modal analysis was carried out for the first version of the system modeling. Calculation of deformations under the action of constant, temporary long-term and short-term loads was performed. A comparison of deflections, horizontal displacements and accelerations of floors with maximum permissible values was carried out.Conclusion. The results of the study allow choosing the optimal variant of the analytical rotational surface. The calculation of deformations under the action of constant, temporary long-term and short-term loads is performed. Comparison of deflections, horizontal displacements and accelerations of floors with maximum permissible values showed that they do not exceed the maximum permissible values.